Mark Twain in Japan : the cultural reception of an American icon - Ishihara, Tsuyoshi, 1971- (Columbia : University of Missouri Press, 2005)
"Explores the history of Mark Twain's reception in Japan in the spheres of books, children's magazines, and anime, the impact of Japanese translations on Twain's public image, how Japanese culture has transformed Japanese versions of Twain's works, and how Japan is culturally influenced by America and America by Japan"--Provided by publisher
What happened to Huck? : Kuni Sasaki's translation of Adventures of Huckleberry Finn -- Mark Twain in wartime Japan : the Samurai version of The prince and the pauper -- Mark Twain in postwar Japan : juvenile translations and school textbooks -- Japanese animations of Huckleberry Finn and Tom Sawyer.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Twain, Mark, -- 1835-1910 -- Appreciation -- Japan; Twain, Mark, -- 1835-1910 -- Translations into Japanese -- History and criticism; Twain, Mark, -- 1835-1910; American literature -- Appreciation -- Japan; Japanese literature -- American influences; Books and reading -- Japan -- History; Criticism -- Japan -- History; Littérature américaine -- Appréciation -- Japon; Littérature japonaise -- Influence américaine.; Livres et lecture -- Japon -- Histoire; Critique -- Japon -- Histoire; LITERARY CRITICISM -- American -- General; American literature -- Appreciation; Art appreciation; Books and reading; Criticism; Japanese literature -- American influences; Japan; Criticism, interpretation, etc; History